Exploring the Principal Curvatures of Ruled Surfaces over Product Time Scales - Suroğlu, Gülden Altay; Yılmaz, Emrah (My University, 2026)
In this study, we present the geometry of ruled surfaces on an arbitrary product time scale. We establish the mean and Gaussian curvatures of these surfaces on the relevant product time scale. Then, we derive the principal curvatures for the ruled surfaces, providing some examples for clarification.
Keywords: Ruled surfaces; partial delta derivatives; Product time scales